2021
DOI: 10.1080/10872981.2021.1892569
|View full text |Cite
|
Sign up to set email alerts
|

Transition-to-residency: pilot innovative, online case-based curriculum for medical students preparing for pediatric internships

Abstract: Background : There is increasing recognition in medical education that greater emphasis must be placed on preparing graduating medical students for their new roles as interns. Few publications in the literature have described transition-to-residency curricula specifically for students interested in pediatrics or pediatric-related fields Approach : We developed novel online pediatric cases, embedded within an innovative, hybrid transition-to-residency course, to address high y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…The performance difference between esotropia and exotropia courses could reflect differences in curriculum efficacy, where some aspects of the case-based material may have been more effective than others [18] . This also aligns with studies from other medical specialties which saw small improvements or no significant differences when comparing flipped classroom to traditional classroom settings with regard to content test scores [15][16][24][25] . In one crossover study, members of three US emergency medicine residency programs demonstrated similar knowledge gained in the flipped classroom model and standard lecture model [24] .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The performance difference between esotropia and exotropia courses could reflect differences in curriculum efficacy, where some aspects of the case-based material may have been more effective than others [18] . This also aligns with studies from other medical specialties which saw small improvements or no significant differences when comparing flipped classroom to traditional classroom settings with regard to content test scores [15][16][24][25] . In one crossover study, members of three US emergency medicine residency programs demonstrated similar knowledge gained in the flipped classroom model and standard lecture model [24] .…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, the Chinese residents indicated that they would like to see the flipped classroom model utilized more frequently and felt that all ophthalmology topics would be appropriate for this teaching style (P-values between 0.008 and <0.001; Figure 2). The higher satisfaction for flipped classroom compared to traditional classroom aligns with other US studies in both medical school [14][15] and graduate medical education [16][17] , including our previously conducted multi-center randomized-control study where 110 US ophthalmology residents preferred the flipped-classroom model over the traditional lecture model [18] . Based on a prior meta-analysis, this preference may result from increasing levels of engagement with the flipped classroom approach as well as a greater focus on personalized teaching [19] .…”
Section: Discussionsupporting
confidence: 72%
“…Two groups have previously reported that synchronous and asynchronous remote bootcamps or transition courses are feasible for supporting the transition between medical school and residency/internship [18,19]. Our study adds to the literature in that our bootcamp focused on the transitional stage from preclinical to clinical in a low-stakes environment.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, continuity of learning environment fosters both patient-centeredness and learnercenteredness [13]. Before clinic internship, the introduction of CBL enables students continuously reinforce their familiarity with a particular disease, thus enhancing the speci c clinical reasoning and interdisciplinary competencies [22].…”
Section: Discussionmentioning
confidence: 99%